A new species of Eurythenes (Crustacea: Amphipoda) from abyssal depths in the Peru-Chile Trench. - Wainwright, Jennifer A.; Weston, Johanna N.j.; Bond, Todd; Jamieson, Alan J. (Zootaxa, 2025)
Eurythenes S.I. Smith in Scudder, 1882 (Crustacea: Amphipoda) are large amphipods found from shallow polar waters to the bottom of subduction trenches. They are key members of the benthopelagic scavenging guild in the deep sea and can swarm baited lander traps. A commonly documented species, Eurythenes gryllus (Lichtenstein in Mandt, 1822) was once considered a widespread cosmopolitan species, but is now recognised as a species complex, with five described cryptic lineages and several others identified but undescribed. One documented but undescribed species has been incorporated into phylogenetic studies as Eurythenes sp. “Peru-Chile Abyssal”. Herein, we formally describe Eurythenes inti sp. nov. as the 11th species within the genus. This species was sampled from 4602 to 6173 m water depth in the northern section of the Peru-Chile Trench, known as the Milne-Edwards sector, during the RV Sonne expedition SO209 in 2010. Eurythenes inti sp. nov. expresses key morphological traits that are diagnostic to this species, including the shape of coxa 2, the dorsal ridging from pereonite 5 to urosomite 1, the subchelate shape of the gnathopod 2 palm, and the three non-protruding nodular spines on the maxilliped inner plate. These morphological features diagnose Eurythenes inti sp. nov. to further clarify this cryptic genus.